Correlation to predict the maximum heat flux of a vertical closed-loop pulsating heat pipe - Kammuang-Lue N. (2014)
The objective of this study is to experimentally investigate the effect of various parameters on the maximum heat flux of a vertical closed-loop pulsating heat pipe (CLPHP) and the inside phenomena that cause maximum heat flux to occur. A correlation to predict the maximum heat flux using the obtained results was also established. Quantitative and qualitative experiments were conducted and analyzed. A copper CLPHP and a transparent high-temperature glass capillary tube CLPHP were used in the quantitative and qualitative experiments. From the study, it was found that when the internal diameter and number of meandering turns increased, the maximum heat flux increased. However, when the evaporator section length increased, the maximum heat flux decreased. The maximum heat flux of a CLPHP occurs due to the dry-out of liquid film at the evaporator section. This occurs after a two-phase working fluid circulation changes flow pattern from countercurrent slug flow to co-current annular flow, because the vapor velocity increases beyond a critical value. A correlation to predict the maximum heat flux obtained from this study was developed.